Alpha-Co(OH)(2)/carbon nanofoam composite as electrochemical capacitor electrode operating at 2 V in aqueous medium - Della Noce, Rodrigo (2016)
In this work, alpha-Co(OH)(2) is electrodeposited onto carbon nanofoam forming a composite electrode operating in a potential window of 2 V in aqueous medium. Prior to electrodeposition, the carbon nanofoam substrate is subjected to a functionalization process, which leads to an increase of about 40% in its specific capacitance value. Formation of cobalt hydroxide clusters onto the functionalized carbon nanofoam by pulse electrodeposition further enhances the specific capacitance of the electrode. The combination of these factors with an enlarged working potential window, results in a material with specific capacitance close to 300 F g(-1) at current density of 1 A g(-1), considering the total mass loading of the composite. This suggests the potential application of the prepared composites in high energy density electrochemical supercapacitors. (c) 2015 Elsevier B.V. All rights reserved.